From data to discovery: technology propels speech-language research and theory-building in developmental science - Laudańska, Zuzanna; Caunt, Anna; Cristia, Alejandrina; Warlaumont, Anne; Patsis, Katerina; Tomalski, Przemysław; Warreyn, Petra; Abney, Drew H.; Borjon, Jeremy I.; Airaksinen, Manu; Jones, Emily JH; Bölte, Sven; et al. (Neuroscience & biobehavioral reviews, 2025)
Research on speech and language development has a long history, but in the past decade, it has been transformed by advances in recording technologies, analysis and classification tools, and AI-based language models. We conducted a systematic literature review to identify recently developed (semi-)automatic tools for studying speech-language development and learners' environments in infants and children under the age of 5 years. The Language ENvironment Analysis (LENA) system has been the most widely used tool, with more and more alternative free- and/or open-source tools emerging more recently. Most studies were conducted in naturalistic settings, mostly recording longer time periods (daylong recordings). In the context of vulnerable and clinical populations, most research so far has focused on children with hearing loss or autism. Our review revealed notable gaps in the literature regarding cultural, linguistic, geographic, clinical, and social diversity. Additionally, we identified limitations in current technology—particularly on the software side—that restrict researchers from fully leveraging real-world audio data. Achieving global applicability and accessibility in daylong recordings will require a comprehensive approach that combines technological innovation, methodological rigour, and ethical responsibility. Enhancing inclusivity in participant samples, simplifying tool access, addressing data privacy, and broadening clinical applications can pave the way for a more complete and equitable understanding of early speech and language development. Automatic tools that offer greater efficiency and lower cost have the potential to make science in this research area more geographically and culturally diverse, leading to more representative theories about language development.
Online verfügbar: 5. Mai 2025, Artikelversion: 8. Mai 2025
Gesehen am 29.10.2025